The consequences of hospital autonomization in Colombia: A transaction cost economics analysis (2013)
Granting autonomy to public hospitals in developing countries has been common over recent decades, and implies a shift from hierarchical to contract-based relationships with health authorities. Theory on transactions costs in contractual relationships suggests they stem from relationship-specific investments and contract incompleteness. Transaction cost economics argues that the parties involved in exchanges seek to reduce transaction costs. The objective of this research was to analyse the relationships observed between purchasers and the 22 public hospitals of the city of Bogota, Colombia, in order to understand the role of relationship-specific investments and contract incompleteness as sources of transaction costs, through a largely qualitative study. We found that contract-based relationships showed relevant transaction costs associated mainly with contract incompleteness, not with relationship-specific investments. Regarding relationships between insurers and local hospitals for primary care services, compulsory contracting regulations locked-in the parties to the contracts. For high-complexity services (e.g. inpatient care), no restrictions applied and relationships suggested transaction-cost minimizing behaviour. Contract incompleteness was found to be a source of transaction costs on its own. We conclude that transaction costs seemed to play a key role in contract-based relationships, and contract incompleteness by itself appeared to be a source of transaction costs. The same findings are likely in other contexts because of difficulties in defining, observing and verifying the contracted products and the underlying information asymmetries. The role of compulsory contracting might be context-specific, although it is likely to emerge in other settings due to the safety-net role of public hospitals. © The Author 2012; all rights reserved.